Levantamiento Fotogramétrico con Dron del Predio Jorge Yánez Castro - López Miranda, Marcel Antonio (2021)
The practice of technology during the last 10 years has been essential in every field, and the agricultural sector has not been the exception. We must know that this device is an unmanned aerial vehicle (UAV), or unmanned aerial system, also called drone. They are equipped with state-of-the-art equipment such as GPS, infrared sensors, high-resolution cameras and radar controls. Drones are capable of sending detailed information to satellites. Which has uses that are of fundamental help at this time in all areas such as: infrastructure inspection, topography, exploration of hard to reach places, caves, cliffs, etc., filming and sports photography, agriculture and other uses. The realization of this work will help to show the latest restorations and achievements that the Jorge Yanez Castro property has obtained, exposing the progress and growth over time. So this project was carried out with the purpose of making a georeferenced topographic survey with photogrammetry of the place under study showing the progress that has been made in the 225 hectares of this property, such as construction of internal roads and platforms to the integral farm, also as the filling of the entrance to Agroindustry, planting of timber trees, etc. Subsequently, we proceeded to the association of the referenced measures, through photographic shots with the drone to form a photo mosaic, which is an image formed by rectangular shots. The consequences of this work determine the progress that Jorge Yanez Castro Farm has had in recent years thanks to the administration of its various delegates who ensure the growth of each of the students so that they feel comfortable and comfortable and can apply the knowledge acquired in our Jorge Yanez Castro Farm.